HUBUNGAN PERSEPSI SISWA TERHADAP PELAKSANAAN ASAS KERAHASIAAN OLEH GURU BK DENGAN MINAT SISWA UNTUK MENGIKUTI KONSELING PERORANGAN - Purwanti, Willi; Firman, Firman; Sano, Afrizal (Universitas Negeri Padang, 2013)
Implementation of individual counseling, guidance and counseling teachers should apply the principle of confidentiality. Reality shows that there are still students who are not open in expressing their concerns. This study aimed to test whether there is a link students' perception implementation of the principle of confidentiality by teacher guidance and counseling with individual counseling student interest. This study belongs to the kind of descriptive correlational. Eleventh grade students study population, sampling using proportional random sampling technique. The results showed there is a significant relationship between students' perceptions of the implementation of the principle of confidentiality by teacher guidance and counseling to interest students to attend individual counseling.